Arrival time distributions of product ions reveal isomeric ratio of deprotonated molecules in ion mobility-mass spectrometry of hyaluronan-derived oligosaccharides - Hermannová, Martina; Iordache, Andreea-Maria; Slováková, Kristína; Havlíček, Vladimír; Pelantová, Helena; Lemr, Karel (Journal of mass spectrometry, 2015)
Hyaluronic acid is a naturally occurring linear polysaccharide with substantial medical potential. In this work, discrimination of tyramine-based hyaluronan derivatives was accessed by ion mobility-mass spectrometry of deprotonated molecules and nuclear magnetic resonance spectroscopy. As the product ion mass spectra did not allow for direct isomer discrimination in mixture, the reductive labeling of oligosaccharides as well as stable isotope labeling was performed. The ion mobility separation of parent ions together with the characteristic fragmentation for reduced isomers providing unique product ions allowed us to identify isomers present in a mixture and determine their mutual isomeric ratio. The determination used simple recalculation of arrival time distribution areas of unique ions to areas of deprotonated molecules. Mass spectrometry data were confirmed by nuclear magnetic resonance spectroscopy.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; ionty; Oligosaccharides; isomerie; Hyaluronic Acid; oligosacharidy; isomer discrimination; nuclear magnetic resonance spectroscopy; Ions; magnetická rezonanční spektroskopie; tyramine-based hyaluronan derivatives; Magnetic Resonance Spectroscopy; mass spectrometry; Isomerism; ion mobility; kyselina hyaluronová